HUBUNGAN EFEK SAMPING OBAT TERHADAP KEPATUHAN MINUM OBAT PADA PASIEN HIV/AIDS DI PUSKESMAS SUKARAJA BANDAR LAMPUNG TAHUN 2025: The Relationship Between Drug Side Effects And Medication Adherence In Hiv/Aids Patients At Sukaraja Health Center, Bandar Lampung, In 2025 - Harissa, Nola; Wahidah, Lilik Koernia; Salsabila, Jauza (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
HIV/AIDS is one of the top infectious diseases that cause death. Side effects of drug use are associated with decreased adherence to medication, where according to the literature, patients who experience unpleasant reactions after taking medication show reduced adherence. Adherence to Antiretroviral treatment is very important to achieve optimal therapeutic results in HIV/AIDS sufferers. The purpose of this study was to determine the relationship between side effects of taking medication and adherence to medication in HIV/AIDS patients at Sukaraja Health Center, Bandar Lampung in 2025. This study used a cross-sectional method with prospective data collection, a sample of 74 patients and the use of purposive sampling for the sampling technique.The Data obtained were analyzed by using the chi-square test to find out the relation between the dependent variable which is medication adherence and the independent variable, namely of drug side effects. The results of the analysis showed that most respondents were aged 26-35 years 34 patients, (45.9%), male 61 patients ( 82.4%), had the highest education level of high school 40 patients (54.1%), and were employed 55 patients (74.3%)This study found medication adherence rates in HIV/AIDS patients based on the MMAS scale, with 48 (64.9%) being adherent and 26 (35.1%) being non-adherent. Twenty-eight (33.8%) patients experienced side effects, while 49 (66.2%) did not. There was a relationship between medication side effects and medication adherence in HIV/AIDS patients with a p-value of 0.030.